99mTc-MIBI Whole Body Scan: A Potentially Useful Technique for Evaluating Metabolic Bone Disease - Al-Shammari, A. M.; Elgazzar, A. H.; Ashkanani, Rasha A. (World Journal of Nuclear Medicine, 2013)
Metabolic bone disease due to hyperparathyroidism is characterized by increased bone resorption and new bone formation. 99mTc- hexakis-2-methoxyisobutylisonitrile (99mTc MIBI) accumulation is controlled by metabolic function and cell viability. To investigate, for the first time, the potential of whole body 99mTc MIBI scan for detecting, visually and with the aid of quantitative analysis, bony changes associated with hyperparathyroidism. Eighty-six patients with hyperparathyroidism, referred routinely for parathyroid localization, were included in this case-control prospective study. Each patient was injected with 20-25 mCi of 99mTc MIBI. Routine anterior cervico-thoracic images were obtained for parathyroid localization. Two extra whole body images were acquired and assessed visually and by drawing regions of interest over the mandible, sternum, femur, humeri, spine, and the soft tissue adjacent to the bone. The ratios of bone to soft tissue were calculated and compared to ratios drawn in a control group routinely referred for cardiac imaging and injected with 99mTc MIBI, after confirming the absence of any bone disease. The visual interpretation of the scans showed 48 patients to have increased bone uptake. Quantitative assessment showed significant difference between the mean ratios of the case and control groups. The Kruskal-Wallis test showed significant agreement between visual and quantitative ratios drawn from delayed right and left femora and left humerus images (P < 0.05). 99mTc MIBI whole body imaging is a potentially useful technique for assessing metabolic bone disease associated with hyperparathyroidism. Quantitative analysis helped in confirming the visual findings.
Keywords: Hyperparathyroidism; metabolic bone disease; 99mTc- hexakis-2-methoxyisobutylisonitrile